The Theater as Stage of Philosophizing: Foundations for a Renewed Pedagogy - Manso, Artur (2015)
The present paper is based on the theatrical universe in its scenic dimension and literary perspective it explores a renewed pedagogy in the teaching of Philosophy at high school. It is intended in this work to highlight the foundations of the investigation that will be carried out at the Balleteatro – Professional School during 2 years with high school students in order to test new Philosophy teaching methodologies through the theatre. We intend therefore to value the close relationship that theatre has always maintained with Philosophy and in that approach to fundament the need for a philosophical education that effectively uses a set of methods and exercises that support the demand of the rational activity that Philosophy obliges as well as the sensorial delight provided by theatre, establishing in this way a closerelationship between the Philosophy teaching and the ethical sensibility and aesthetics training of students.